perceptions of heads of families towards the requirements of child empowerment in the era of the fourth industrial revolution - Abouelhaded , fatma Aly; Abd elsattar Fahmy , Manal (Social Empowerment Journal, 2023)
The study aims to identify the perceptions of heads of families to the nature of the era of the Fourth Industrial Revolution and the extent of their awareness of its features and risks to the child, and to identify the requirements for self- and objective empowerment, by following the survey method and applying a Questionnaire journalist sample of (384) single heads of households in the cities. distance education and the virtual teacher, and the child may be exposed to several risks, including; Technological addiction, loss of self-confidence, exposure to pornography and violence, and the concept of child empowerment includes a set of abilities and skills that include the child’s ability to self-learning via the Internet, and that the most important requirements for self-empowerment of the child are the development of positive attitudes for the child Towards the use of technology, promoting the values of electronic culture, raising the child’s awareness of the risks of dealing with technology, and developing the child’s skills in the field of self-management and cooperation with others. As for the requirements of objectively empowering the child, they include facilitating the child’s ownership of modern technology, and to include in educational curricula the concepts of artificial intelligence and nanotechnology.